ضمان التوازن المالي للصفقات العمومية في التشريع الجزائري - زيدان, جلال الدين; عليــــــان عصام, جلال الدين (جامعة الوادي university el-oued, 2020)
تأسيسا على ما تقدم في دراسة الموضوع، فإن ضمان التوازن المالي نشأ في مواجهة السلطات الواسعة التي تتمتع بها المصلحة المتعاقدة في تعديل شروط تنفيذ الصفقة العمومية، وبالرغم من إعتراف المشرع الجزائري للمصلحة المتعاقدة بمجموعة من السلطات كسلطة تعديل العقد، ومراجعة الأسعار وتحيينها، بالإضافة إلى إستعمال الملحق كألية للحفاظ على التوازن المالي، فهذا لا يمنع المتعامل المتعاقد للإستناد على القوانين والنظريات التي أسسها الفقه والقضاء، والذي أخذ بها المشرع الجزائري كأساس يكفل به حقوق الطرفين( المصلحة المتعاقدة ـ المتعامل المتعاقد). إن زيادة إلتزامات المتعامل المتعاقد مع المصلحة المتعاقدة نتيجة تدخلها لتعديل شروط الصفقة، والذي يكون الهدف منه المصلحة العامة وسير المرفق العام بإنتظام وإطراد، هذا ما يؤثر على التوازن المالي للصفقة العمومية ، مما يقود كلا الطرفين الى إستعمال مجموعة من الوسائل والأليات للحفاظ على ذلك التوازن التي أقرتها القوانين، قانون الصفقات العمومية وتفويضات المرفق العام وقانون الإجراءات المدنية والإدارية، سواءاً المتعلقة بألية التسوية الودية التي تكون بطرق سريعة وغير مكلفة ومربحة للوقت، أما في حالة الإنسداد وعدم الوصول إلى الحل بهذه الألية، فإن اللجوء إلى القضاء يعد الوسيلة الثانية (التسوية القضائية) التي يمكن من خلالها إعطاء لكل من الطرفين حقه في الصفقة ومن ثم الحفاظ على ذلكم التوازن. Based on the above in the study of the subject, the guarantee of financial balance arose in the face of the broad powers enjoyed by the contracting interest in amending the terms of the implementation of the public deal, despite the Algerian legislator’s recognition of the contracting interest to a group of authorities as the authority to amend the contract, review and update prices, in addition to using The appendix as a mechanism to maintain financial balance, this does not prevent the contracting customer to rely on the laws and theories based on jurisprudence and the judiciary, which the Algerian legislator took as a basis by which he guarantees the rights of the two parties (the contracting authority - the contracting customer). An increase in the obligations of the contractor customer with the contracting interest as a result of its intervention to amend the terms of the deal, which is the goal of the public interest and the functioning of the public facility regularly and steadily, this affects the financial balance of the public deal, which leads both parties to use a set of means and mechanisms to maintain that balance that was Approved by laws the law of public procurement and the mandates of the public attachment, the civil and administrative procedures law, Whether related to the friendly settlement mechanism that is fast, inexpensive and profitable for time, and in the case of blockage and lack of access to the solution with this mechanism, resorting to the judiciary is the second means (judicial settlement) by which each of the two parties can be given their right to the deal and then preserve On that balance.
مذكرة ماستر
Keywords: االملحق .المصلحة; Appendix. Interest